2012
DOI: 10.1021/la204452p
|View full text |Cite
|
Sign up to set email alerts
|

Ag/AgBr/Graphene Oxide Nanocomposite Synthesized via Oil/Water and Water/Oil Microemulsions: A Comparison of Sunlight Energized Plasmonic Photocatalytic Activity

Abstract: In this article, we report that Ag/AgBr nanostructures and the corresponding graphene oxide (GO) hybridized nanocomposite, Ag/AgBr/GO, could be facilely synthesized by means of a surfactant-assisted assembly protocol, where an oil/water microemulsion is used as the synthesis medium. We show that thus-produced nanomaterials could be used as highly efficient and stable plasmonic photocatalysts for the photodegradation of methyl orange (MO) pollutant under sunlight irradiation. Compared with the bare Ag/AgBr nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
138
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 203 publications
(142 citation statements)
references
References 41 publications
3
138
0
Order By: Relevance
“…This could be attributed to the existence of GO nanosheets in the synthesis system [28][29][30]. Structurally, GO nanospecies are atomic thick nanosheets of covalently organized lattice of carbon atoms, whose basal planes and edges are decorated with various oxygen-containing groups, such as hydroxyl, epoxide, carboxyl groups, etc [32,33].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridmentioning
confidence: 99%
See 4 more Smart Citations
“…This could be attributed to the existence of GO nanosheets in the synthesis system [28][29][30]. Structurally, GO nanospecies are atomic thick nanosheets of covalently organized lattice of carbon atoms, whose basal planes and edges are decorated with various oxygen-containing groups, such as hydroxyl, epoxide, carboxyl groups, etc [32,33].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridmentioning
confidence: 99%
“…In the case of GO nanosheets, the introduction of the covalently attached hydrophilic oxygen groups on their basal plane endows them with amphiphilic properties to some extent. Accordingly, this makes it possible that GO nanospecies could play a role as an unconventional polymeric surfactant in a colloid system [30,32,33]. On the other hand, from the viewpoint of nanofabrication, it has been demonstrated that the size of the produced nanostructures in a colloid system could be decreased by introducing polymeric surfactant molecules to the synthesis system [30,[34][35][36][37][38][39][40].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridmentioning
confidence: 99%
See 3 more Smart Citations